The Epic of Evolution and a Theology of Sacramental Ecology - McDuffie, David C. (Religions, 2019)
The 'Epic of Evolution' is the scientific story that reveals that we live in an approximately 14-billion-year-old universe on a planet that is approximately 4.6 billion years old and that we are a part of the ongoing process of life that has existed on Earth for 3.5-4 billion years. This article focuses on the religious and ecological significance of the evolutionary epic in an effort to seamlessly connect the ecological value attributed as a part of an understanding of the evolutionary connectedness of life on earth with the Divine grace understood to be present in Christian sacramental worship. With a particular emphasis on the Eucharist, I argue that the sacramental perspective of grace being conveyed through material reality provides the potential for Christian sacramental tradition to make a significant contribution to protecting the threatened ecological communities of our planet. By incorporating William Temple's concept of a 'sacramental universe,' I propose that the grace that is understood to be present in the substances of the bread and wine of the Eucharist points outward so that it can also be witnessed in all of God's ongoing Creation. When the Eucharist is understood as taking place in a sacramental universe from which ecological grace flows; the incarnation can be recognized not as a one-time event but as an ongoing sacramental process through which God is revealed through the perpetual emergence of life. Consequently, as the primary form of sacramental worship in Christian tradition, the Eucharistic witness to the incarnation of God in Jesus and thanksgiving for life overcoming death provide Christians with a ritual orientation for recognizing the incarnational presence of God as an ever-present reality potentially witnessed in all that is. Therefore, the formal sacrament of the Eucharist is a part of a broader sacramental ecology of earthly life in which the presence of Divine grace can be witnessed in all aspects of the natural order. As a result, connecting Eucharistic grace with the value associated with an awareness of the ecological and genetic connectedness of all forms of life serves as a mutual enrichment of sacramental tradition and contemporary efforts to protect life on Earth.